Defective Collagen-Induced Platelet Aggregation in a Normal Population - ten Cate, J. W; de Vries, S. I; Sixma, J. J; van Berkel, W (Thrombosis and Haemostasis, 1971)
Systemic studies on platelet functions of normal healthy individuals were carried out in two independent centres. Both samples of 40 volunteers comprised several individuals (Amsterdam 3 and Utrecht 5 individuals) with a syndrome consisting of an absent collagen-induced platelet aggregation, a reversible ADP-aggregation and frequently a decreased platelet retention in the glass bead column. Occasionally the platelet factor-3 availability was decreased.